Pengembangan Buletin Mitigasi Gempa Bumi Terintegrasi Ayat-Ayat Al-Qur’an di SMAN 1 Polewali - Suhardiman, Suhardiman; Hafid, Erwin; Widyawati, Widyawati (UIN Alauddin Makassar, 2021)
This type of research is research and development (R&D) with the Borg & Gall Development model which consists of the information-gathering stage, the planning stage, the initial form development stage, the preparatory field test, the preparation field test revision, and the main field test. This study aims to develop an integrated earthquake mitigation bulletin with verses of the Koran that meet the valid and effective criteria for grade XI students of SMA Negeri 1 Polewali. The research instruments used were validation sheets and student and educator response questionnaires to the bulletin. The data obtained were then analyzed using qualitative and quantitative analysis. The results showed that the newsletter met the valid criteria with an average value of 0.80. Student responses are in the positive category and educators' responses are in the very positive category so that the bulletin meets the criteria for being effective and worthy of being used as a learning medium in class. This type of research is research and development (R&D) with the Borg & Gall Development model which consists of the information-gathering stage, the planning stage, the initial form development stage, the preparatory field test, the preparation field test revision, and the main field test. This study aims to develop an integrated earthquake mitigation bulletin with verses of the Koran that meet the valid and effective criteria for grade XI students of SMA Negeri 1 Polewali. The research instruments used were validation sheets and student and educator response questionnaires to the bulletin. The data obtained were then analyzed using qualitative and quantitative analysis. The results showed that the newsletter met the valid criteria with an average value of 0.80. Student responses are in the positive category and educators' responses are in the very positive category so that the bulletin meets the criteria for being effective and worthy of being used as a learning medium in class.